2018
DOI: 10.1094/mpmi-01-18-0003-r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chemotaxis Compounds in Root Exudates and Their Sensing Chemoreceptors in Plant-Growth-Promoting Rhizobacteria Bacillus amyloliquefaciens SQR9

Abstract: Chemotaxis-mediated response to root exudates, initiated by sensing-specific ligands through methyl-accepting chemotaxis proteins (MCP), is very important for root colonization and beneficial functions of plant-growth-promoting rhizobacteria (PGPR). Systematic identification of chemoattractants in complex root exudates and their sensing chemoreceptors in PGPR is helpful for enhancing their recruitment and colonization. In this study, 39 chemoattractants and 5 chemorepellents, including amino acids, organic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 46 publications
3
96
0
Order By: Relevance
“… Note: Apart from the 116 compounds listed in this Table; there is evidence for the presence of at least 72 other compounds that, however, could not be identified. Compounds identified as attractants or repellents (r) in a previous study (Feng et al, ) are shown in bold. Chemicals detected in this study but absent in the previous study are underlined. a .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Note: Apart from the 116 compounds listed in this Table; there is evidence for the presence of at least 72 other compounds that, however, could not be identified. Compounds identified as attractants or repellents (r) in a previous study (Feng et al, ) are shown in bold. Chemicals detected in this study but absent in the previous study are underlined. a .…”
Section: Resultsmentioning
confidence: 99%
“…From the chemotaxis and colonization data it is clear that McpA and McpC are central receptors. A previous study has identified the ligands for both receptors (Feng et al, ). From the 188 compounds detected in root exudates at the cotyledon stage, McpA and McpC were found to respond to 29 compounds of which 28 served as chemoattractants while capric acid was a repellent (Feng et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that the benzoxazinoid 2,4‐dihydroxy‐7‐methoxy‐2 H ‐1,4‐benzoxazin‐3(4 H )‐one (DIMBOA) producing wild‐type maize attracted significantly higher numbers of P. putida than the DIMBOA‐deficient bx1 mutant . Sometimes bacteria are also attracted by a blend of chemo‐attractants secreted by plants, for example the PGPBs Bacillus amyloliquefaciens and Pseudomonas fluorescens are attracted by amino acids and organic acids produced by cucumber and tomato roots …”
Section: Roles Played By Plant Signaling Molecules In the Soil Ecosystemmentioning
confidence: 99%